2021
DOI: 10.1177/0192513x21993187
|View full text |Cite
|
Sign up to set email alerts
|

Does Locus of Control Influence Parentification and Anxiety in Father–Daughter Relationships?

Abstract: Parentification is a role-reversal phenomenon in which boundary violations occur such as children being their parents’ physical or emotional caretakers. Researchers have shown that childhood parentification can produce anxiety, but locus of control (LOC) moderates this relationship. We sought to examine the influence of LOC on the parentification-anxiety relationship in father–daughter dyads, as this dyad is under-represented in the parentification literature. One hundred and eighty-one undergraduate women com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…Moreover, the LOC partially mediated the relationship between anxious attachment and all three psychopathology symptom clusters (social anxiety, OCD, and depression) at various levels. More specifically, the relationship between LOC and anxiety has been the subject of interest in the literature since the 1960s (e.g., Butterfield, 1964;Cohen et al, 2008;Hovenkamp-Hermelink et al, 2019;Jolley & Spielberger, 1973;Mays & Krueger, 2021;Molinari & Khanna, 1981;Rubin, 1993;Shoychet et al, 2022;Watson, 1967). Furthermore, the growing body of literature review has shown a positive relationship between belief in external LOC and psychopathology (Atilola et al, 2021;Dag, 1999;Moreira et al, 2020;Sullivan et al, 2017Sullivan et al, , 2021.…”
Section: Relationships Between Loc and Anxietymentioning
confidence: 99%
“…Moreover, the LOC partially mediated the relationship between anxious attachment and all three psychopathology symptom clusters (social anxiety, OCD, and depression) at various levels. More specifically, the relationship between LOC and anxiety has been the subject of interest in the literature since the 1960s (e.g., Butterfield, 1964;Cohen et al, 2008;Hovenkamp-Hermelink et al, 2019;Jolley & Spielberger, 1973;Mays & Krueger, 2021;Molinari & Khanna, 1981;Rubin, 1993;Shoychet et al, 2022;Watson, 1967). Furthermore, the growing body of literature review has shown a positive relationship between belief in external LOC and psychopathology (Atilola et al, 2021;Dag, 1999;Moreira et al, 2020;Sullivan et al, 2017Sullivan et al, , 2021.…”
Section: Relationships Between Loc and Anxietymentioning
confidence: 99%